The Analysis of the Correlation between the Degree of Market Concentration and the Level of Consumer Protection - Ştefania-Cristina Curea; Eduard Dinu; Paul Prisecaru (Amfiteatru Economic Journal, 2017)
The common aim of legislation in the field of competition and consumer protection is to ensure the consumers' sovereignty and well-being. Based on the analysis of literature in this field we have established, as the main focus of our research, a study of the correlation between the degree of market concentration and the level of consumer protection. By using regression analysis applied to data collected from two sectors of activity, respectively the compulsory civil liability insurance for car owners and mobile telecommunications, we have shown that there is a direct correlation, meaning that a high degree of market concentration – which indicates a low competition level, leads to a decrease in the level of consumer protection.
Keywords: C21; L13; L96; G22; 330; degree of market concentration; level of consumer protection; compulsory civil liability insurance for car owners; mobile telecommunications